Plants and gardens as artefacts in transcultural contexts
1 online resource
Keywords: This edited volume explores the ways in which the object biography or object itinerary approach could be adapted to frame research on animate objects, such as plants and gardens in transcultural contexts. By treating these animate elements as 'objects' in the manner of artefacts and looking at their individual histories, we gain a more nuanced sense of how data accumulated, how new knowledge developed through printed texts and specimen collections, and how the creators of gardens or landscapes formed their collections. Chapters explore the shifts in meanings when objects from diverse origins meet in new cultural contexts where their new owners create assemblages based on their perception of the world. The book will be of interest to scholars working in art history, material culture, and cultural geography.